Assessment and comparison of phytochemical constituents and biological activities of bitter bean (Parkia speciosa Hassk.) collected from different locations in Malaysia - Ghasemzadeh, Ali; Hawa Z. E., Jaafar; Mohamad Fhaizal, Mohamad Bukhori; Mohd Hafizad, Rahmat; Asmah, Rahmat (BioMed Central Ltd., 2018)
Background: Parkia speciosa seeds are a common ingredient in Malay cuisine with traditional interest because of its medicinal importance and content of health-promoting phytochemicals. This study evaluated the phytochemical constituents and biological activities (antioxidant and antibacterial activities) of Parkia speciosa Hassk seeds collected from three different regions of Malaysia (Perak, Negeri Sembilan and Johor). Phytochemical constituents (total flavonoid and total phenolic) were measured using the spectrophotometric method, and individual flavonoids and phenolic acids were identified using ultra-high-performance liquid chromatography. Ferric reducing antioxidant potential (FRAP) assay and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay we used in order to evaluation of antioxidant activities. Disc diffusion method was employed for the evaluation of antibacterial activity of extracts against Gram-positive and Gram-negative bacterial strains. Results: The primary screening of phytochemicals showed that P. speciosa seeds contain alkaloids, terpenoids, flavonoids, and phenolics. Samples collected from Perak contained the highest levels of the phytochemical constituents, with highest DPPH and FRAP activity followed by Negeri sembilan and Johor. From the identified compounds, quercetin and gallic acid were identified as the most abundant compounds. Seeds collected from the Perak location exhibited potent antibacterial activity, against both Gram-positive and Gram-negative bacteria strains. Staphylococcus aureus and Bacillus subtilis were recorded as the bacterial strains most sensitive to P. speciosa seed extracts. Correlation analysis showed that flavonoid compounds are responsible for the antioxidant activities of the P. speciosa seeds studied, while antibacterial activity showed a high correlation with the levels of gallic acid. Conclusions:Parkia speciosa seed grown in Perak exhibit the highest concentrations of phytochemicals, as well as the highest biological activity. It may also be recommended for the food industry to use seeds from this area for their products, which are going to compete in the expanding functional food markets. © 2018 The Author(s).